Avoid plagiarism. Respect the author (Gaceta Técnica, 2018)
In the world of scientific publications, it is essential to keep in mind the so-called “copyright”. It is a somewhat common practice to find in various works sent by the Editorial Committee of a scientific journal to the evaluators for their respective review, copies of fragments or complete texts reflected in other works already published; this belies the academic reliability of the author, whether he did it consciously, or simply out of simple ignorance. Therefore, it is required to make public knowledge what is the appropriate practice when wanting to reflect in the context of a manuscript the original ideas of another author.
Keywords: plagiarism; copyright